The Influence Of Population Growth And Education On Unemployment And Poverty In East Kalimantan - Lily Mulyati; Eny Rochaida; Diana Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to determine the effect of The Influence of Population Growth and Education on Open Unemployment and Poverty in East Kalimantan. The data used is secondary time series data for 2012 – 2022 obtained from the BPS of East Kalimantan Province. Using the SPSS 25 analysis tool with the path analysis method, this study concludes that there is a direct effect of population growth and unemployment has not effect and education level on unemployment has an effect. Population growth, education level and unemployment have a significant influence on economic growth in East Kalimantan Province. Then, the indirect influence of population growth and unemployment on economic growth through unemployment in East Kalimantan has not an effect.